Spinal Deformities in Adolescents, Adults and Older Adults - Bettany-Saltikov, Josette; Kandasamy, Gokulakannan (IntechOpen, 2021)
Spinal Deformities in Adolescents, Adults and Older Adults is a unique book with a wide scope of coverage of the topic. Written by specialists worldwide, this book presents under-reported topics and treatments in spinal deformity, as well as a very interesting autobiographical case study from one of the authors detailing his self-management approach to his own spinal deformity. The chapters examine the evidence relating to spinal deformities together with assessment tools, treatment modalities, and the various types, benefits, and side effects of these diverse treatment approaches. This book is designed for clinicians working with patients, researchers, and patients and their families.